Water entry of grooved spheres: Effect of the number of grooves and impact velocity. (January 2021) - Mehri, Ali; Akbarzadeh, Pooria
Abstract: In this paper, the results of an experimental investigation of the normal impact of grooved spheres on a calm water surface are presented. Particular attention is given to describe the air cavity formation when the number of grooves and the impact velocity change. All experimental tests are conducted in a constant surrounding fluid Bond number, Capillary length using grooved spheres with constant diameter but in various impact, Reynolds and Froude numbers, and the trajectory of spheres is visualized by a high-speed camera at 1 ∼ 2 kfps frame rate. This study extends the recent paper (Mehri and Akbarzadeh, 2020) that first investigated the water entry of grooved spheres, by considering higher impact velocities. The study introduces the role of grooves in the air entrainment cavity formation and shows the dependence of the cavity characteristic such as upper and underlying cavity shape, vertical upward and downward reentrant jets, and splash curtain shape on the number of grooves and the impact velocity. Also, the effect of the number of grooves on and sphere kinetics like descent trajectory, velocity, and acceleration is discussed. Highlights: The water entry of grooved spheres is experimentally investigated. The role of grooves on the air entrainment cavity formation is highlighted. The cavity dynamics is studied when the grooves number and impact velocity change. Effect of grooves number on sphere kinetics at some impact velocities is studied.